2023
DOI: 10.1002/berj.3853
|View full text |Cite
|
Sign up to set email alerts
|

The importance of school culture in supporting student mental health in secondary schools. Insights from a qualitative study

Abstract: Schools have the potential to provide a place of education and sanctuary for children and young people of all backgrounds. The rise in mental health problems in children and young people in the wake of the COVID-19 pandemic, particularly in relation to growing inequities, means that identifying ways in which schools can help respond to this growing mental health crisis demands urgent attention. This paper reports on case studies carried out in two London comprehensive schools, exploring how aspects of school c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…However, without clear guidance on what kinds of mental wellbeing support were to be provided, there was variation between the schools. These differences in school provision of supports echo findings from a 2021 qualitive paper about school culture and mental health in COVID-19 in London, identifying that there was no standard of provision, and much was down to individual school motivation and resourcing (Barker et al, 2023).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, without clear guidance on what kinds of mental wellbeing support were to be provided, there was variation between the schools. These differences in school provision of supports echo findings from a 2021 qualitive paper about school culture and mental health in COVID-19 in London, identifying that there was no standard of provision, and much was down to individual school motivation and resourcing (Barker et al, 2023).…”
Section: Discussionmentioning
confidence: 73%
“…Furthermore, researchers have advocated for holistic ‘whole school’ approaches to mental health support for these groups that were particularly badly impacted by the pandemic (Barker et al, 2021). A study looking at how school culture supported student mental health provision in two London schools during the COVID-19 pandemic identified that the leadership of schools and available resources were important in determining what was provided and also signalled that consideration of the mental health needs of staff alongside those of students was essential (Barker et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The school is a place where young people spend a lot of time on a daily basis, so the school's handling of such emergencies has a direct impact on the mental health situation. Various factors affecting students' mental health were evaluated in terms of both positive and negative impacts of school culture on students' mental health [15]. Jenkins, E. K. et al argued that students in the nursing program are subjected to common pressures from multiple sources, such as their personal academic careers and so on, which can lead to threats to students' mental health.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence that school-based interventions can have beneficial effects on adolescent mental well-being and associated behavioural outcomes (eg, sleep, physical activity, classroom behaviour and attainment) 38–41. Whole-school environment interventions that promote lifestyles conducive to good health are reported to have a more pronounced effect on mental well-being than individual approaches targeting knowledge and beliefs 38 42.…”
Section: Introductionmentioning
confidence: 99%